(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Transplanting and fertilizer application for rice production in Bangladesh are tedious, time consuming and laborious task, and mostly done manually. Mechanical transplanting of rice becoming popular in the country in recent years and few machines have been developed for granular urea deep placement, however, having some limitations. Placing granular urea precisely along with rice transplanting, an attempt was under taken to design and fabricate an electronic control granular urea applicator to be attach with a 4-row walk behind type rice transplanter. Fabrication of the electronic granular urea applicator was done in the workshop of the Department of Farm Power and Machinery, Bangladesh Agricultural University, Mymensingh. Physical structure of the attachment was assembled with available parts of BARI granular urea applicator. A DC gear motor was coupled with metering disk shaft to rotate and pick granular urea from hopper. Moreover, its speed was synchronized with the picker speed of the rice transplanter by a microcontroller Arduino Mega 2560. A computer program was developed and compiled successfully into Arduino IDE, where an equation was derived and incorporated into loop control structure. The program can also be used for any kind of applications where variable rate is required. The machine was found successful in test run and laboratory-based experiments. Average spacing of granular urea placement was found 34.71 cm with 1.38% missing hill, Its power requirement was found about 20 W. This innovation provided options for performing granular urea application and rice transplanting, two most laborious tasks simultaneously which might minimize the cost of production as well as human drudgery with an error free manner. J Bangladesh Agril Univ 17(3): 380–387, 2019